Microbial, Physical, and Chemical Changes in Galveston Bay Following an Extreme Flooding Event, Hurricane Harvey - Steichen, Jamie L.; Labonté, Jessica M.; Windham, Rachel; Hala, David; Kaiser, Karl; Setta, Samantha; Faulkner, Patricia C.; Bacosa, Hernando; Yan, Ge; Kamalanathan, Manoj; Quigg, Antonietta (Frontiers in Marine Science, 2020)
Hurricane Harvey (category 4 storm) made landfall along the coast of Texas (USA) and then stalled out over Texas and Louisiana, releasing 1.29 x 1011 m3 of precipitation over 5 days. This caused extensive flooding that elevated freshwater river discharge and land runoff into Galveston Bay and eventually into the Gulf of Mexico. The floodwaters delivered a significant influx of terrigenous dissolved organic matter, organic pollutants and nutrients along with terrestrial and freshwater associated microbes. Over the 24 days following the flooding event, samples were collected on five cruises across Galveston Bay from the mouth of the San Jacinto River (Houston, TX) to the Gulf of Mexico. Parameters measured for this study include: water quality (temperature, salinity, pH and dissolved oxygen), nutrients (NO3-, NO2-, NH4+, Pi, and HSiO3-), polycyclic aromatic hydrocarbons, pharmaceuticals (cotinine, carbamazepine, carbamazepine-epoxide, and prednisone), biocide (imidacloprid), dissolved organic carbon, lignin phenols, bacteria and the eukaryotic community (16S and 18S rRNA genes). In the week after the flood event, bay-wide salinities decreased to 0-5 compared to the higher pre-Harvey salinities of 20-30 (recorded 5 days before the flood). Water treatment facilities and petrochemical plants were compromised due to the heavy flooding in the region. This led to increased concentrations of nutrients, polycyclic aromatic hydrocarbons, pharmaceuticals and biocides across Galveston Bay immediately following the storm. In the 4 weeks following the storm, concentrations of nutrients and organic pollutants began to decrease coinciding with rising salinities as the freshwater was flushed into the Gulf of Mexico and seawater began moving back into the Bay. Successive blooms of chlorophytes, diatoms, and dinoflagellates occurred similar to post-storm communities from past hurricanes that have impacted estuarine systems along the Gulf of Mexico. The eukaryotic community changed substantially following Harvey and did not recover to pre-Harvey conditions during our study period, suggesting a longer recovery time compared to the prokaryotes. Although the water quality parameters and microbial community showed signs of returning to pre-Harvey conditions within the month following the flood event, long-term impacts need to be measured in the years following the flood.